Menggambar Garis dan Lingkaran dengan Algoritma Bresenham - teguh susyanto (STMIK Sinar Nusantara, 2010)
In computer graphics, graphic depiction of the complex forms is actually composed of a group of primitive objects in an image area, so that the whole will form a particular object. Depictions of these objects are actually a primitive generating clusters of adjacent pixel color according to the form object to be depicted. The forms of the simplest object that can underlie complex graphical form is an object lines and circles. There are several famous primitive methods for drawing lines and circles that is using either the Digital Differential Analyzer (DDA) or Bresenham algorithms. In this paper the author tries to present the implementation of Bresenham's method to draw the line and circle with Delphi.Key words: line, circle, Bresenhams Algorithms